2018
DOI: 10.1002/path.5103
|View full text |Cite
|
Sign up to set email alerts
|

EnLIGHTenment of tumor vessel normalization and immunotherapy in glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a highly vascularized and aggressive brain tumor. Despite aggressive standard care, GBM remains predominantly fatal; hence, new innovative therapies are required. Recent research published in the Journal of Pathology has identified the CGKRK peptide as a promising tool with which to specifically target the tumor vasculature from high-grade glioma. This tumor vessel-homing peptide was fused to the tumor necrosis factor superfamily member LIGHT/TNFSF14, and injected intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Macrophages and T cells have been deemed essential for HEV and TLS formation ( 83 , 113 ) ( Figure 3A ). LIGHT-VTP in combination with ICB therapy can produce intratumoral memory T cells and Teff cells and improve prognosis ( 114 ). In addition, LIGHT-VTP combined with anti-VEGF and ICB therapy can increase the frequency of HEVs and normalize tumor vessels and the accumulation of T cells in glioblastoma and lung metastases ( 115 , 116 ).…”
Section: Development Of Multiple Approaches To Induce the Tls Formationmentioning
confidence: 99%
“…Macrophages and T cells have been deemed essential for HEV and TLS formation ( 83 , 113 ) ( Figure 3A ). LIGHT-VTP in combination with ICB therapy can produce intratumoral memory T cells and Teff cells and improve prognosis ( 114 ). In addition, LIGHT-VTP combined with anti-VEGF and ICB therapy can increase the frequency of HEVs and normalize tumor vessels and the accumulation of T cells in glioblastoma and lung metastases ( 115 , 116 ).…”
Section: Development Of Multiple Approaches To Induce the Tls Formationmentioning
confidence: 99%
“…HEVs can be differentiated from other blood vessels by their expression of PNAd glycoproteins, recognized by a group of antibodies. These antibodies have resulted in the identification of ectopically formed HEVs in organs affected by inflammatory conditions, autoimmune diseases, or cancers [10,[14][15][16][17][18][19][20][21][22][36][37][38][39][40][41]55,64,74].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high endothelial venules (HEVs) appeared, and T cell infiltration also increased. 109 Increasing studies have shown that immune cells also play roles in tumor vessel normalization. Thus, stimulation of such immune cells may be a new strategy to normalize the tumor vasculature.…”
Section: Tactics For Normalization Of Tumor Blood Vesselsmentioning
confidence: 99%